Предмет: Алгебра,
автор: MsKnopka
Помогите прошу!!!
Пользуясь формулой куба разности, преобразуйте в многочлен выражения:
(1-2с)^3
(2а-3)^3
Ответы
Автор ответа:
0
(1-2c)³(2a-3)³=(1³-6×1²×c+12×1×c²-8c³)×(8a³-36a²+18a-21)=(1-6c+12c²-8c³)×(8a³-36a²+18a-21)
Автор ответа:
0
(1-2с)³=1³-3*1²*2с+3*1*(2с)²-(2с)³=1-6с+12с²-8с³
(2а-3)³=(2а)³-3*(2а)²*3+3*2а*3²-3³=8а³-36а²+54а-27
(2а-3)³=(2а)³-3*(2а)²*3+3*2а*3²-3³=8а³-36а²+54а-27
Похожие вопросы
Предмет: Геометрия,
автор: Аноним
Предмет: Українська література,
автор: 1234567891011111133
Предмет: История,
автор: davrushevkamil
Предмет: Геометрия,
автор: Olysh
Предмет: Математика,
автор: irusik080